Investigating the factors influencing Generation-Y attitudes toward fast-food consumption in Ipoh City / Amy Nurnajwa Puhad ... [et al.] - Puhad, Amy Nurnajwa; Ahmad Russlin, Elyssa Maisara; Mohd Khamis, Nor Farawahidah; Abu Bakar, Ahmad Redhuan; Ab Aziz, Wan Siti Nor Azma (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Although there are various adverse effects that are already known, some fast food remains popular with consumers. The aim of this study was to investigate the factors that influence the attitudes of Generation Y towards fast food consumption in Ipoh City. The study focused on three main factors, namely convenience, health consciousness, and trust. The study used a quantitative analysis approach, relying on statistical evidence to draw conclusions. The results indicated that convenience, health consciousness, and trust were the key factors that influence Generation-Y attitudes towards fast-food consumption. This study provides valuable insights into the factors that affect consumer attitudes towards fast food consumption among Generation Y individuals in Ipoh City. The findings can contribute to a better understanding of the preferences and motivations of this demographic segment, which can be useful for fast-food industry stakeholders in developing targeted marketing strategies and product offerings. Nevertheless, limitations due to the online survey method used during the pandemic could potentially lead to biased responses and time-consuming data collection. The quantitative approach limited the collection of information, suggesting the need for qualitative or mixed-method approaches for more specific data. The study's focus on Generation Y in Ipoh City is another limitation, urging future research to consider other generations and regions.